Insect pests of cowpeas - Jackai, L.E.N.; Daoust, R.A. (1986)
Cowpeas (blackeye peas, or simply beans in many parts of Africa), Vigna unguiculata, are widely grown in the tropics and subtropics for human as well as for animal food. Nigeria, Brazil, and Niger are among the major producers and account for over 70% of the world crop (137, 174). Nigeria alone produces ca 900,000 tons annually (172). Grown mainly as a secondary crop in association with other staples such as maize, sorghum, millet, and cassava, cowpeas constitute the cheapest source of dietary protein and energy for most poor people in the tropical world (132). They are eaten as green seeds, green pods, and dry grains, and tender leaves are used as a vegetable (101, 104, 132). In addition, the haulm is fed to cattle in a number of countries (132). ...